2021
DOI: 10.3390/ijerph18168703
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Psychoeducation Program to Foster Chinese Primary School Students’ Covitality

Abstract: This investigation evaluated the Growth Psychoeducation Intervention (GPI) designed to increase primary school students’ covitality, a construct describing the beneficial combinatorial effects of positive psychological skills and mindsets. Students with higher covitality levels have stronger relationships with their teachers and classmates, and behave in more positive ways. This GPI intervention study employed a pretest-posttest-follow quasi-experimental design to evaluate a culturally adapted group counseling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Psychoeducational is one of the intervention programs that has been effectively assisting individuals in decreasing their anxiety and helping them in increasing their mental health [20][21]. A study in China showed that psychoeducational program reducing bullying victimization in Chinese primary school students [22].…”
Section: Introductionmentioning
confidence: 99%
“…Psychoeducational is one of the intervention programs that has been effectively assisting individuals in decreasing their anxiety and helping them in increasing their mental health [20][21]. A study in China showed that psychoeducational program reducing bullying victimization in Chinese primary school students [22].…”
Section: Introductionmentioning
confidence: 99%